As safe as houses? : Israel's demolition of Palestinian homes - Amnesty International (2010)
Palestinians living under Israeli occupation in East Jerusalem and the rest of the West Bank face such tight restrictions on what they can build that their rights to adequate housing is being violated. The Israeli authorities condemn as "illegal" homes and other structures built without permits that they control and rarely allow to Palestinian residents, and then order their destruction. Demolition crews, accompanied by security officials, may arrive at any time, giving families little notice or opportunity to remove their possessions.